2012
DOI: 10.1542/peds.2011-2140
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Expectations of Canadian Parents Who Bring Febrile Children for Medical Care

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Fever phobia is a ubiquitous problem throughout the world. As a result, fever is pharmacologically overtreated, and medical attention is frequently sought by worried parents. WHAT THIS STUDY ADDS:Most Canadian parents fear their child' s fever, resulting in aggressive surveillance and treatment. Parents expect information about fever etiology and how to care for their ill child. Few parents expect antibiotics and satisfaction with care is high. abstract OBJECTIVES: The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
51
2
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 30 publications
12
51
2
10
Order By: Relevance
“…He found that 30% of parents could not define normal temperature. 8 Similar results were reported by Purssell"s et al a decade later. Durousseau et al found that 42% parents knew fever threshold which is in agreement with the present study.…”
Section: Awarenesssupporting
confidence: 83%
See 2 more Smart Citations
“…He found that 30% of parents could not define normal temperature. 8 Similar results were reported by Purssell"s et al a decade later. Durousseau et al found that 42% parents knew fever threshold which is in agreement with the present study.…”
Section: Awarenesssupporting
confidence: 83%
“…6 Many parents administer antipyretics even when there is minimal or no fever, because they are concerned that the child must maintain a "normal" temperature. 8 Harmful effects of fever alone are rare and are found mainly in very ill and compromised children or in children with fever persisting for more than 5 days, high core temperature (> 39°C) and fever in an infant less than 1 ~ 2 months of age or when it is associated with signs of severe underlying disease. 6 Fever may be useful as a defence mechanism as the body's immune response can be strengthened at higher temperatures; however, there are arguments for and against the usefulness of fever, and the issue is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were analyzed using the American Academy of Pediatrics (AAP) and National Institute for Health and Clinical Excellence (NICE) recommendations [2,15]. A substantial proportion of parents in our study held unrealistic concerns about fever and its consequences, and most used antipyretics excessively, both of which were common findings in other studies as well [4][5][6][7][8][9][10][11][12]. Increased use of antipyretics and wrong external cooling methods to reduce fever, waking sleeping febrile children to administer antipyretics, and routine use of antipyretics before and after vaccination reflects heightened concern about the harmful effects of fever.…”
Section: Discussionmentioning
confidence: 96%
“…Although fever is a beneficial host response, it is an important cause of anxiety for parents and leads to undue and excessive use of antipyretics [2,3]. For more than three decades, beginning with a survey conducted by Schmitt in 1980, researchers have demonstrated significant degrees of "fever phobia" in caregivers from different countries [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%